2004
DOI: 10.1128/aem.70.1.610-612.2004
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Reliable Method To Precipitate Proteins from Bacterial Culture Supernatant

Abstract: A simple and reliable method for precipitating protein from bacterial culture supernatants based on a pyrogallol red-molybdate-methanol (PRMM) protocol has been developed and applied for the analysis of proteins secreted by a bacterial type III secretion system. PRMM-based precipitation has been shown to be more efficient and robust than are conventional protocols.Recently, bacterial mechanisms for protein secretion have become an important focus of research due to the observation that key virulence factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The amount of the ToxA chimeric proteins produced by the bacteria was determined by linear regression from a representative immunoblot with a mouse anti-TGFα monoclonal antibody (Clone MF9; Abnova, Taipei, Taiwan) and a secondary goat anti-mouse alkaline phosphatase antibody (Jackson Laboratories). Preliminary assays of VNP20009 wild type ToxA and ToxA chimeras showed that the chimeric ToxA supernatants required 200 mL of supernatant concentrated by pyrogallol red molybdate methanol (PRMM) precipitation (Caldwell and Lattemann, 2004) in order to be detected, whereas 10 mL the wild type ToxA supernatant could be detected without concentration, and thus these volumes were utilized. The relative amount of epidermal growth factor receptor (EGFR) was determined using a polyclonal rabbit anti-EGFR antibody (Rockland, Gilbertsville, PA) against 20 µg each of the respective tumor cell lysate, where the lysate total protein concentration was determined by the BCA assay (Pierce/Thermo Fisher) and the relative quantity of EGFR determined by immunoblot.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of the ToxA chimeric proteins produced by the bacteria was determined by linear regression from a representative immunoblot with a mouse anti-TGFα monoclonal antibody (Clone MF9; Abnova, Taipei, Taiwan) and a secondary goat anti-mouse alkaline phosphatase antibody (Jackson Laboratories). Preliminary assays of VNP20009 wild type ToxA and ToxA chimeras showed that the chimeric ToxA supernatants required 200 mL of supernatant concentrated by pyrogallol red molybdate methanol (PRMM) precipitation (Caldwell and Lattemann, 2004) in order to be detected, whereas 10 mL the wild type ToxA supernatant could be detected without concentration, and thus these volumes were utilized. The relative amount of epidermal growth factor receptor (EGFR) was determined using a polyclonal rabbit anti-EGFR antibody (Rockland, Gilbertsville, PA) against 20 µg each of the respective tumor cell lysate, where the lysate total protein concentration was determined by the BCA assay (Pierce/Thermo Fisher) and the relative quantity of EGFR determined by immunoblot.…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were centrifuged and the medium was removed and passed through a 0.2-mpore-size filter. Proteins in the filtrate were precipitated overnight, and the protein pellet was sedimented by centrifugation at 10,000 ϫ g for 1 h, washed twice with cold acetone, and resuspended in 50 l of SDS sample buffer (6). Proteins were separated by SDS-PAGE and identified by peptide mass fingerprinting.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomic Analysis of Proteins in the Culture SupernatantsTo detect proteins that are present in culture supernatants, a method utilizing pyrogallol red-molybdate-methanol was used as described previously (40). Briefly, supernatants were isolated by centrifugation from stationary cultures (16 h, A 600 about 4) of N⌬eps and parental wild-type strain of V. cholerae N16961 grown in LB medium, filtered through 0.2-m nylon filters (Fisher), followed by high speed centrifugation (170,000 ϫ g, 4°C, 3 h) to remove outer membrane vesicles.…”
Section: Methodsmentioning
confidence: 99%